Lactiplantibacillus plantarum monolayer enhanced bactericidal action of carvacrol: biofilm inhibition of viable foodborne pathogens and spoilage microorganisms - Poscente, Valeria; Di Gregorio, Luciana; Costanzo, Manuela; Nobili, Chiara; Bernini, Roberta; Garavaglia, Luigi; Bevivino, Annamaria (Frontiers in Microbiology, 2023)
The prevalence of biofilm-associated microorganisms and the increasing use of ready-to-eat fresh products represent the current duality the food industry must address. Innovative and eco-friendly antibiofilm solutions and appropriate microbiological food control systems are urgently needed to improve food quality and safety. This work aimed to investigate the in vitro combined efficacy of carvacrol with a pre-formed biofilm monolayer of the probiotic Lactobacillus plantarum DSM 20174. The antimicrobial activity against both planktonic and sessile cells of food pathogenic and spoilage strains was investigated. Integration of flow cytometry (FCM) with culture-based methods was applied to monitor cells' cultivability and viability during biofilm-forming activity. The results showed that L. plantarum pre-formed biofilm monolayer enhanced the antimicrobial effect of carvacrol determining a bactericidal action while the treatment alone induced the viable but not culturable (VBNC) cell state only. Furthermore, the great efficacy of the combined treatment allowed to application a lower concentration of carvacrol (100 ppm) to achieve significant damage in cell viability. In conclusion, the incorporation of carvacrol with L. plantarum pre-formed biofilm represents a promising alternative for an antimicrobial functionalised ready-to-eat packaging.